AGRONOMIC TRAITS OF MAIZE HYBRIDS IN NARROW ROW SPACING: 2005 OFF SEASON - SCHWANTES, Diogo Oswaldo; SCHUELTER, Adilson Ricken; FONTOURA, Darci da; MAROCHIO, Josiani (Scientia Agraria, 2007)
The present work had the objective to evaluate the effect of narrow row spacing on agronomic traits in four maize hybrids planted in the off season, in an experiment conducted during the 2005 agricultural year in Toledo, west of Paraná. The experimental design was a completed randomized block, with four replications, in a 4x2 factorial scheme having as factors the hybrid (30F80, 30K75, 30P70, X1392D) and the row spacings (0,38 m and 0,76 m). The plant population was 60.000 plants ha-1, independent of the utilized treatments. As a result of the row narrowing, a significant increase in the trait mass of thousand grains was observed. However, in the trait stalk lodging it had showed a negative influence, being dependent on the hybrids with horizontal leaf architecture. Other variables as average plant high, average ear high, stalk base diameter, diameter in the insertion of the first ear, plant lodging and the grain yield only showed significant difference in relation to the hybrids. Among the hybrids, the X1392D and 30F80 showed the bests performances, being the most suitable for the off season plantings.